PEMBENTUKAN NILAI KARAKTER GOTONG ROYONG PADA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS V - Juliana Putri Irmawanti; Rury Rizhardi; Hermansyah Hermansyah (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
ABSTRACT Pancasila Education in elementary schools is expected not only to foster students' conceptual understanding but also to provide meaningful learning experiences that cultivate the value of mutual cooperation in authentic situations. In practice, however, students' habits of collaborating, demonstrating social concern, and sharing responsibilities have not consistently developed, indicating the need for learning activities that connect collaborative experiences with contexts familiar to their daily lives. This study examined the process of fostering mutual cooperation character values through a project involving the creation of an Ampera Bridge wall decoration in a fifth-grade classroom at SD Negeri 60 Palembang. A descriptive qualitative approach was employed, with data collected through observations, interviews, questionnaires, and documentation. The data were analyzed using data reduction, data display, and conclusion drawing, supported by source and technique triangulation to enhance the trustworthiness of the findings. The learning process demonstrated the development of collaboration, empathy, and responsibility as students worked together to complete the project. Questionnaire findings revealed that one student was classified in the very good category, nineteen students in the good category, and four students in the fair category, with an overall achievement score of 87.77%, categorized as very good. Character development was strengthened by students' positive habits, teachers' guidance, parental support, and peer interaction, whereas family circumstances, the school environment, excessive technology use, and individualistic tendencies emerged as inhibiting factors. These findings indicate that collaborative project-based learning integrating local cultural contexts effectively strengthens the internalization of mutual cooperation character values while making Pancasila Education more contextual and meaningful for elementary school students. ABSTRAK Pembelajaran Pendidikan Pancasila di sekolah dasar diharapkan tidak hanya membangun pemahaman konseptual, tetapi juga menghadirkan pengalaman belajar yang mampu menumbuhkan karakter gotong royong dalam situasi nyata. Kenyataannya, pembiasaan bekerja sama, menunjukkan kepedulian, dan berbagi tanggung jawab belum selalu berkembang secara optimal sehingga diperlukan pembelajaran yang mengaitkan aktivitas kolaboratif dengan konteks yang dekat dengan kehidupan peserta didik. Penelitian ini memusatkan perhatian pada proses pembentukan nilai karakter gotong royong melalui projek pembuatan hiasan dinding Jembatan Ampera di kelas V SD Negeri 60 Palembang. Kajian dilaksanakan menggunakan pendekatan kualitatif deskriptif dengan memanfaatkan observasi, wawancara, angket, dan dokumentasi sebagai sumber data yang dianalisis melalui reduksi data, penyajian data, serta penarikan kesimpulan yang diperkuat dengan triangulasi sumber dan teknik. Dinamika pembelajaran memperlihatkan berkembangnya kerja sama, empati, dan tanggung jawab selama peserta didik terlibat dalam penyelesaian projek secara berkelompok. Hasil angket menunjukkan 1 siswa berada pada kategori sangat baik, 19 siswa kategori baik, dan 4 siswa kategori cukup, dengan capaian keseluruhan sebesar 87,77% pada kategori sangat baik. Pembentukan karakter dipengaruhi oleh pembiasaan positif peserta didik, peran guru, pola asuh orang tua, dan interaksi antarteman, sedangkan lingkungan keluarga, lingkungan sekolah, penggunaan teknologi yang berlebihan, serta kecenderungan perilaku individualistis menjadi faktor penghambat. Temuan ini menegaskan bahwa aktivitas kolaboratif berbasis projek yang memanfaatkan budaya lokal mampu memperkuat internalisasi nilai karakter gotong royong sekaligus menjadikan pembelajaran Pendidikan Pancasila lebih kontekstual dan bermakna bagi peserta didik sekolah dasar.